Promiscuous potato: elucidating genetic identity and the complex genetic relationships of a cultivated potato germplasm collection - Anglin, Noelle L.; Chavez, Oswaldo; Soto - Torres, Julian; Gomez, Rene; Panta, Ana; Vollmer, Rainer; Durand, Marisol; Meza, Charo; Azevedo, Vania; Manrique - Carpintero, Norma C.; Kauth, Philip; Coombs, Joesph J.; et al. (Frontiers in Plant Science, 2024)
DEprimary investigator responsible for initiating the project, leading it and being active in all phases of the work. OCstatistician involved in all data analysis. JS -DNA extractions, field work, and data analysis. RGdiversity assessment of samples to fingerprint, field work, maintenance and characterization of mother plant material, and taxonomic determinations. APmaintenance and provision of tissue culture plants and guided project. PK provision of seed saver germplasm and interpretation of data. MD, CMfield work, maintenance and characterization of mother plant material, and taxonomic determinations. RV, NM, VAediting manuscript, involvement in identity verification, germplasm curation\maintenance, and interpretation of data. JJC and DSDgenotyping of seed saver material and analysis support. NLAco-PI, project design, drafted